Pengaruh Model Pembelajaran Radec Terhadap Hasil Belajar IPA Siswa Kelas V SD Inpres 7/83 Bune Kecamatan Libureng Kabupaten Bone - Harmianti Harmianti; Irmawanty Irmawanty; Muh. Erwinto Imran (Journal Innovation In Education, 2023)
The purpose of this study was to determine the effect of the RADEC learning model on the science learning outcomes of fifth grade students at SD Inpres 7/83 Bune. This type of research is a type of quantitative research or quasy experiment Nonequivalent Control Group Design. The sample and population are fifth grade students at SD Inpres 7/83 Bune, Bone Regency, totaling 40 students. The instruments in this study were tests and documentation.Based on the research results and data analysis, it can be concluded that the use of the RADEC learning model in learning has an effect on science learning outcomes in class V SD Inpres 7/83 Bune, Bone Regency. This is evident in the acquisition of the posttest average score of the experimental group's learning outcomes using the RADEC learning model compared to the acquisition of the average score in the control group students without using the RADEC learning model. The average posttest score of the experimental group was 84.5 and that of the control group was 54.7. This gain was strengthened based on the results of hypothesis testing using the T-test showing the condition for the results of t count > t table, namely 3.338 > 2.016 with the results of the hypothesis H0 being rejected and H1 being accepted. This proves that the use of the RADEC learning model has an effect on science learning outcomes in fifth grade students at SD Inpres 7/83 Bune, Bone Regency.